Comparative Studies on Adsorption of Congo Red (CR) by Low Cost Adsorbents Prepared from Different Varieties of Melon Seeds - Iqbal, Nida; Imran, Muhammad; Iqbal, Javed; Mahmood, Zaid (Asian Journal of Chemistry, 2010)
The comparative ability of melon, water melon and musk melon seeds as adsorbents for Congo red dye in aqueous solution was studied. The experiments were done as batch processes. The main objective of the study was to investigate the influence of adsorbent dose, contact time, stirring speed, pH and temperature on adsorption process performance. Acidic pH (2), low temperature (20-30 ºC) and low stirring speed (100-200 rpm) were found to be favorable conditions for the adsorption of Congo red dye by all the three adsorbents. The maximum adsorption 98.5 % at 50 min, 98.2 % at 30 min and 98.1 % 40 min has been observed for melon, musk melon and water melon seeds, respectively at low adsor-bent dose (0.15 g). The adsorption capacity of melon seed was found to be 23.10 mg, 21.23 mg/g for musk melon seed and 3.08 mg/g for water melon seed. The adsorption equilibrium process has been described well by using Langumir and Fruendlich adsorption isotherms. It can be concluded from this study that melon seed can best be used as an adsorbent for the removal of Congo red dye from its aqueous solution as compared to watermelon and musk melon seeds.